Ethno-federalism: Challenges and opportunities - Juhász József (Međunarodni Problemi)
The study analyses the role of federalism in solving the national and ethnic conflicts. From this point of view it describes the main types of modern federal state: mononational (e.g. USA, FRG), multiethnic (Switzerland, present-day Russia) and multinational forms (former socialist federations, present-day Bosnia-Herzegovina). Hereafter the study outlines the most important views which appeared in the modern political thinking about the role of federalism in solving the national and ethnic conflicts. It refers to the messianistic federalist ideologies, to the French republican tradition, and to the American liberal approach. Furthermore it describes the main characteristics of socialist federations, briefly analyses the causes of their disintegration. Finally the study sums up the most important stabilizing factors of ethno-federations.